2019
DOI: 10.1038/s41598-019-44861-5
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival dysbiosis in mucosa-associated lymphoid tissue lymphoma

Abstract: To investigate the conjunctival microbiota and the association between the development of conjunctival mucosa-associated lymphoid tissue (MALT) lymphoma and dysbiosis, DNA samples were collected from 25 conjunctival MALT lymphoma patients and 25 healthy controls. To compare the microbiota, samples were collected from the following four body locations: conjunctiva, meibomian gland, periocular skin and hand. Extracted DNA was analyzed by 16S rRNA sequences, and libraries were sequenced on an Illumina MiSeq seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…1,[21][22][23] Since 2001, and especially over the past decade, a number of articles have been published regarding the analysis of the conjunctival microbiome via the use of 16S rRNA gene sequencing. 14,15,[24][25][26][27][28][29][30][31] However, and to the best of our knowledge, no previous studies have reported analyzing the detailed microbiome of meibum via 16S rRNA gene sequencing, 32,33 so it has yet to be elucidated. Although one published study did investigate the meibomian gland microbiome via 16S rRNA gene sequencing for the strain once isolated from the culture of the meibum, some of the dominant anaerobic commensal bacteria, such as P. acnes, were not detected in that meibum.…”
mentioning
confidence: 99%
“…1,[21][22][23] Since 2001, and especially over the past decade, a number of articles have been published regarding the analysis of the conjunctival microbiome via the use of 16S rRNA gene sequencing. 14,15,[24][25][26][27][28][29][30][31] However, and to the best of our knowledge, no previous studies have reported analyzing the detailed microbiome of meibum via 16S rRNA gene sequencing, 32,33 so it has yet to be elucidated. Although one published study did investigate the meibomian gland microbiome via 16S rRNA gene sequencing for the strain once isolated from the culture of the meibum, some of the dominant anaerobic commensal bacteria, such as P. acnes, were not detected in that meibum.…”
mentioning
confidence: 99%
“…This study found no significant difference in diversity between the TAO and control groups, which was similar to allergic rhinoconjunctivitis ( Yau et al., 2019 ), Sjögren’s syndrome ( de Paiva et al., 2016 ), and conjunctival mucosa-associated lymphoid tissue lymphoma ( Asao et al., 2019 ). The reason for this result may be related to the small sample size of the control group in this study, which reduced the statistical power.…”
Section: Discussionmentioning
confidence: 63%
“…Of note, two anophthalmic sockets had detectable Clostridium sequences while none was seen in contralateral control eyes. Clostridium sequences have been detected occasionally in previous studies as a component of normal conjunctiva 3 , 19 .…”
Section: Resultsmentioning
confidence: 83%